Religion as a “grammar of peace”. Reflections around interculturality and religion in the thought of Raúl Fornet Betancourt - SANTASILIA , Stefano (Utopía y Praxis Latinoamericana, 2022)
The problem of interreligious dialogue finds a specific place in the reflection of the philosopher Raúl Fornet Betancourt. The same possibility of intercultural dialogue involves the need for a reflection on that experience that most embodies the constellation of values that is at the base of a culture, that is, the religious experience. For this reason, based on the guidelines for a possible dialogue between the different religious positions, indicated by the Cuban thinker in his deep reflection dedicated to intercultural philosophy, an attempt will be made to bring to light the possible short circuits and the horizons still to be unrevealed for the development of a possible “grammar of peace”.